2021
DOI: 10.1039/d1tb00018g
|View full text |Cite
|
Sign up to set email alerts
|

An anti-aggregation NIR-II heptamethine-cyanine dye with a stereo-specific cyanine for imaging-guided photothermal therapy

Abstract: Due to the hydrophobicity of the cyanine dye and the huge conjugated plane, the cyanine dye is prone to H-aggregation in the aqueous solution, and the ultraviolet absorption is blue-shifted....

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(20 citation statements)
references
References 39 publications
0
20
0
Order By: Relevance
“…The total sample size of individual studies and the number of cases with different efficacy were further calculated by reviewed the included studies and the supplementary literatures. Of the 42 studies, 11 items confirmed that tumors could be completely ablated by photothermal treatment ( 15 18 , 30 , 33 , 38 , 48 51 ). And 20 items showed conspicuous reduction in tumor size but not complete elimination ( 8 , 15 , 16 , 19 , 20 , 23 , 25 , 30 , 32 , 34 36 , 38 – 41 , 47 , 48 , 50 , 51 ).…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations
“…The total sample size of individual studies and the number of cases with different efficacy were further calculated by reviewed the included studies and the supplementary literatures. Of the 42 studies, 11 items confirmed that tumors could be completely ablated by photothermal treatment ( 15 18 , 30 , 33 , 38 , 48 51 ). And 20 items showed conspicuous reduction in tumor size but not complete elimination ( 8 , 15 , 16 , 19 , 20 , 23 , 25 , 30 , 32 , 34 36 , 38 – 41 , 47 , 48 , 50 , 51 ).…”
Section: Resultsmentioning
confidence: 98%
“…Of the 42 studies, 11 items confirmed that tumors could be completely ablated by photothermal treatment ( 15 18 , 30 , 33 , 38 , 48 51 ). And 20 items showed conspicuous reduction in tumor size but not complete elimination ( 8 , 15 , 16 , 19 , 20 , 23 , 25 , 30 , 32 , 34 36 , 38 – 41 , 47 , 48 , 50 , 51 ). Compared with the control group, tumors treated with periodic PTT could eventually be completely ablated with some degree of crusting [n=108, RR=7.01, 95%CI (3.04, 16.13), P<0.00001; Heterogeneity: Tau 2 = 0.00, Chi 2 = 1.93, df=10 (P=1.00), I 2 = 0%] ( Figure 3A ).…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…Generally, it can be further divided into first near-infrared (NIR-I, 650–950 nm) and second near-infrared (NIR-II, 1,000–1700 nm) fluorescence imaging ( Qi et al, 2018 ; Kubicek-Sutherland et al, 2020 ; Moreno et al, 2020 ; Shinn et al, 2021 ). Although possessing a better signal-to-noise ratio and depth-to-resolution ratio, NIR-II fluorophores still show deficiencies in stability, quantum yield, and biocompatibility ( Bhavane et al, 2018 ; Kenry et al, 2018 ; Qian et al, 2021 ; Kang et al, 2022 ). Hence, FI which we have mentioned in this review refers to NIR-I fluorescence imaging.…”
Section: Introductionmentioning
confidence: 99%